Radiofrequency Ablation: A Nursing Perspective - Locklin, Julia K. (2005)
Radiofrequency ablation (RFA) has emerged as a safe and predictable technology for treating certain patients with cancer who otherwise have few treatment options. Nurses need to be familiar with all phases of the RFA procedure to create an optimal environment for patients. This article offers a brief review of the RFA procedure and nurses' responsibilities in caring for these patients. Before RFA, nurses should focus on patient education and aggressive hydration. During the procedure, nurses can prevent injury by placing grounding pads appropriately, monitoring vital signs, and medicating patients as needed. After RFA, nurses should assess the skin puncture site, provide adequate pain relief, and, again, hydrate patients. Nurses who care appropriately for RFA recipients may help to improve patient outcomes and make an otherwise frightening procedure more comfortable.